Bithalamic hyperintensity on T2-weighted MR: vascular causes and evaluation with MR angiography. - Bell, D A; Davis, W L; Osborn, A G; Harnsberger, H R (American Journal of Neuroradiology, 1994)
PURPOSE To determine whether MR angiography can be used to differentiate between the two vascular causes of bithalamic hyperintensity on T2-weighted MR images: "top of the basilar" artery occlusion and deep cerebral vein thrombosis. METHODS A retrospective review identified six patients with bithalamic T2 hyperintensity of vascular causes. MR angiography was performed in four patients, MR angiography and conventional angiography in one patient, and conventional angiography in one patient. Data pertaining to clinical presentation and hospital course were collected. MR angiographic techniques were multislab overlapping three-dimensional time-of-flight, 2-D time-of-flight, and 2-D phase-contrast. RESULTS Three cases of top of the basilar artery occlusion and three cases of deep cerebral vein thrombosis were recognized. In all cases, T2 hyperintensity in a vascular distribution suggested cerebral occlusive disease. Infarction involving the thalami and basal ganglia was present in two cases of deep cerebral vein thrombosis. Infarction of the thalami, mesodiencephalic region, and cerebellar hemispheres was present in two cases of basilar artery occlusion. Bithalamic infarction alone was seen in one case of deep cerebral vein thrombosis and one case of basilar artery occlusion. In the five cases in which MR angiography was used, this technique accurately distinguished the vessels involved (arterial or venous). CONCLUSION MR angiography is a useful adjunct to MR imaging in the evaluation of bithalamic T2 hyperintensity. It does help distinguish between the two vascular causes: top of basilar artery occlusion and deep cerebral vein thrombosis.